State-level trends in infant and young child feeding practices and child undernutrition in India: An ecological analysis of three rounds of National Family Health Survey - Rajarshi Pandey; Rupsa Banerjee (Journal of Allied Health Sciences & Medical Research, 2026)
Child undernutrition remains a major public health concern in India, despite sustained efforts over the past two decades. While national-level improvements have been reported, substantial variation persists across states. This descriptive ecological study analysed state- and union territory-level data from three rounds of the National Family Health Survey (NFHS-3, 2005–06; NFHS-4, 2015–16; and NFHS-5, 2019–21). Trends in underweight, stunting, and wasting among children under five years of age were assessed. States and Union Territories were classified based on underweight trajectories as either sustained decrease or mixed/increasing trend. Percentage-point changes were calculated for selected IYCF and maternal health indicators, and average changes were compared across state groups. In addition, selected social and contextual indicators were descriptively examined to provide a broader perspective on the enabling environment for child nutrition. Results showed that, at the national level, underweight and stunting declined across survey rounds, whereas wasting showed slower and less consistent improvement. Substantial inter-state variation was observed. States with sustained declines in underweight prevalence generally showed more favourable improvements in breastfeeding practices and maternal healthcare utilization compared with states showing mixed or increasing trends. However, anaemia among women remained persistently high. Social and contextual indicators, including women’s participation in decision-making, financial inclusion, and sanitation coverage, showed improvement over time, although adverse conditions such as spousal violence and low maternal BMI persisted. India has made measurable progress in reducing child undernutrition, but improvements remain uneven and incomplete. Strengthening maternal nutrition, improving early-life care, and addressing structural inequalities will be essential for achieving sustained and equitable improvements in child nutrition outcomes.